Geographical distance and barriers explain population genetic patterns in an endangered island perennial. (18th August 2015) - Dias, Elisabete F.; Moura, M.; Schaefer, H.; Silva, Luís
Abstract : Oceanic islands are of particular importance for the conservation of global diversity. Rare island plants with small population sizes and unique genetic patterns resulting from prolonged evolutionary isolation are usually extremely fragile. Therefore, research dedicated to conservation of these plants should consider threat factors, population structure and genetic diversity to enable the development of scientifically supported management programs. For Lactuca watsoniana, Azorean lettuce, we performed a comprehensive population genetic study, unravelling genetic diversity patterns intrinsically related to geographical distances and barriers. Our study showed that genetic diversity levels in island plants can be relatively high even for rare plants. Abstract: Island plants are frequently used as model systems in evolutionary biology to understand factors that might explain genetic diversity and population differentiation levels. Theory suggests that island plants should have lower levels of genetic diversity than their continental relatives, but this hypothesis has been rejected in several recent studies. In the Azores, the population level genetic diversity is generally low. However, like in most island systems, there are high levels of genetic differentiation between different islands. The Azores lettuce, Lactuca watsoniana, is an endangered Asteraceae with small population sizes. Therefore, we expect to find a lower level of genetic diversity than in the other more common endemic Asteraceae. The intra- and interpopulation genetic structure and diversity of L. watsoniana was assessed using eight newly developed microsatellite markers. We included 135 individuals, from all 13 known populations in the study. Because our microsatellite results suggested that the species is tetraploid, we analysed the microsatellite data (i) in codominant format using PolySat (Principal Coordinate Analysis, PCoA) and SPAgedi (genetic diversity indexes) and (ii) in dominant format using Arlequin (AMOVA) and STRUCTURE (Bayesian genetic cluster analysis). A total of 129 alleles were found for all L. watsoniana populations. In contrast to our expectations, we found a high level of intrapopulation genetic diversity (total heterozigosity = 0.85; total multilocus average proportion of private alleles per population = 26.5 %, F is = −0.19). Our results show the existence of five well-defined genetic groups, one for each of the three islands São Miguel, Terceira and Faial, plus two groups for the East and West side of Pico Island ( F st = 0.45). The study revealed the existence of high levels of genetic diversity, which should be interpreted taking into consideration the ploidy level of this rare taxon.